1997
DOI: 10.1002/(sici)1097-0061(19970915)13:11<1029::aid-yea160>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Two New S-Phase-Specific Genes fromSaccharomyces cerevisiae

Abstract: Two new yeast genes, ASF1 (Anti‐Silencing Function) and ASF2, as well as a C‐terminal fragment of SIR3, were identified as genes that derepressed the silent mating type loci when overexpressed. ASF2 overexpression caused a greater derepression than did ASF1. ASF1 overexpression also weakened repression of genes near telomeres, but, interestingly, ASF2 had no effect on telomeric silencing. Sequences of these two genes revealed open reading frames of 279 and 525 amino acids for ASF1 and ASF2, respectively. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 52 publications
14
169
0
1
Order By: Relevance
“…1A). Consistent with a role for Asf1 in chromatin assembly during NER, yeast asf1 mutants are sensitive to UV irradiation [36].…”
Section: Chromatin Assembly During Excision Repairmentioning
confidence: 57%
See 2 more Smart Citations
“…1A). Consistent with a role for Asf1 in chromatin assembly during NER, yeast asf1 mutants are sensitive to UV irradiation [36].…”
Section: Chromatin Assembly During Excision Repairmentioning
confidence: 57%
“…Yeast lacking Asf1, CAF-1 or INO80 activity have profound viability problems in response to DNA damaging agents [13,36,38,41,43]. A closer examination of the cell cycle stage where the CAF-1 and asf1 mutants yeast die following double-strand DNA repair shows that they permanently arrest at metaphase due to activation of the DNA damage checkpoint leading to cell death [41,94] (our unpublished observations).…”
Section: The Consequences Of Failure To Assemble and Disassemble Chromentioning
confidence: 77%
See 1 more Smart Citation
“…Another histone chaperone, Asf1, is associated with the HIR complex (Green et al 2005). Null mutants in components of the HIR complex do not have a growth phenotype (Sherwood et al 1993), but asf1D cells grow poorly (Le et al 1997).…”
Section: Negative Regulation Of the Histone Genesmentioning
confidence: 99%
“…Asf1 was first identified in a genetic screen based on its ability to disrupt transcriptional silencing in budding yeast when overexpressed (Le et al, 1997). Later, it was shown that Asf1 was a histone chaperone functioning in both replication-coupled and replicationindependent nucleosome assembly (Tyler et al, 1999).…”
Section: The Function Of Three Histone Chaperones In Rc Nucleosome Asmentioning
confidence: 99%